An experimental study of tensile property variability in selective laser melting. (July 2019) - Zhang, Shanshan; Rauniyar, Santosh; Shrestha, Subin; Ward, Aaron; Chou, Kevin
Abstract: This study investigated the variability of mechanical properties of Ti-6Al-4V (Ti64) alloy fabricated by selective laser melting (SLM) with different process conditions. The objective is to examine the effects of various process conditions, including the energy density in fabrications, and the build orientation and location, on the porosity and the mechanical properties of SLM specimens. A small-scaled tensile specimen model was designed and fabricated in an SLM system using commercial Ti64 powder. During the fabrication experiment, a near-infrared (NIR) camera was employed to acquire thermal images for the post-process melt-pool analysis. The as-built specimens were then CT-scanned for the porosity analysis and tested using a tensile testing machine to obtain Young's modulus, yield strength and ultimate tensile strength. The analysis of variance (ANOVA) was utilized to identify significant factors and interactions of different factors to SLM-build mechanical properties. The results can be summarized as follows. For the range of the conditions tested, all 3 factors appear significant to the mechanical properties except Young's modulus, which seems insensitive to any factors in the range tested. The elongation exhibits a significantly larger value for vertical-build specimens, in addition to its increase with the decrease of the energy density. Moreover, some second-order interactions are significant to the ultimate tensile strength, but not to the yield strength. The porosity severity is governed by the energy density, and the build direction and location only influence the porosity slightly. It was also found that the mechanical properties approach the greatest values when the energy density used was at the medium level (55.6 J/mm 3 ) instead of the high level (83.4 J/mm 3 ), which resulted in the highest porosity due to keyhole formations. The NIR result also shows that the melt pool size is correlated with the energy density; the higher the energy density, the longer the melt pool, though the melt pool width remains similar.